21st Century Character Values of Elementary School Students - Mardius, Ali; Morelent, Yetty; Poro, Suci; Fitria, Mona; Salsabila, Salsabila; Paboja, Yudi (Indonesian Journal of Sport Management, 2025)
The purpose of this study is to reveal the 21st Century characters possessed by Elementary School students. This study uses survey research and descriptive methods. The research data were obtained by distributing questionnaires to students in grades 5 and 6 from 2 Elementary Schools in Padang City. The collected data were tabulated and analyzed to determine the values ​​of the 21st Century characters possessed by students. The results of this study indicate that the 21st Century characters, namely moral and performance characters possessed by Elementary School students, are in the adequate category. These character values ​​tend to have the same value for each indicator, both performance and morals. The kinar character at the level of persistence in learning and positive attitudes in learning have values ​​in the low category. While in the moral character value, all indicators are in the adequate category. This value shows that there needs to be awareness of how to improve students' character to face the 21st Century. Such as providing character-based learning models in every subject at school.